A phase II trial of bendamustine, carboplatin, and dexamethasone for refractory or relapsed peripheral T-cell lymphoma (BENCART trial). Issue 13 (10th November 2019) - Park, Byeong-Bae; Kim, Won Seog; Suh, Cheolwon; Hong, Jung Yong; Yang, Deok-Hwan; Lee, Won Sik; Do, Young Rok; Koh, Young Il; Won, Jong-Ho; Kim, Min Kyoung; Jo, Jae-Cheol; Hyun, Shin Young; et al.
Abstract: This trial was designed to investigate the efficacy and toxicity of bendamustine, carboplatin, and dexamethasone (BCD) for relapsed or refractory peripheral T-cell lymphomas (PTCLs), which would be expected to exhibit more promising clinical outcomes compared with bendamustine therapy alone. After treatments with BCD, eight patients exhibited a complete response (CR; 29%) and seven exhibited a partial response (PR; 25%). The overall response rate (ORR) was 54%. Five patients proceeded to ASCT and three patients finally achieved CR. The median progression-free survival (PFS) was 4.4 months (2.8–6.0, 95% CI). For a total of 85 cycles of BCD, grade 3 or 4 neutropenia, thrombocytopenia, and anemia occurred in 17.6, 38.8, and 16.5% of cycles, respectively. Only one patient experienced febrile neutropenia. BCD was a considerable salvage regimen for relapsed or refractory PTCLs with acceptable toxicity; AITL or ASCT eligible patients were more effective to BCD. Trial registration: ClinicalTrials.gov identifier: NCT02424045.